ISLAMIC EDUCATION AND THE EMANCIPATION OF DISABLED INDIVIDUALS - Raus, Norakyairee Mohd (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2022)
In this study, emancipation refers to the release of the paradigm or the provision of equal (fair) rights to the disabled individual (Orang Kurang Upaya) community based on an appreciation of the reality of disability. In contemporary social studies, the